PENGARUH PENGALAMAN AUDITOR, KOMPLEKSITAS TUGAS, DAN INDEPENDENSI AUDITOR TERHADAP AUDIT JUDGMENT - Angeliani, Angeliani (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2025)
The quality of audit judgment is the most important factor to ensure the accuracy and credibility of financial statements. Therefore, this study aims to determine the effect of auditor experience, task complexity, and auditor independence on audit judgment at Public Accounting Firms (KAP) in the Jakarta area. This study is expected to contribute in providing recommendations for auditors in improving their abilities by having sufficient work experience, having diverse and complex tasks related to task complexity, and professional ethics as an auditor related to auditor independence. This type of research is quantitative research whose data sources come from primary data. Data collection was carried out by distributing questionnaires to auditors working at KAP in the Jakarta area. Data analysis was carried out using Smartpls software and the Partial Least Square (PLS) data analysis method. The results of this study indicate that independence has a positive effect on audit judgment, while auditor experience and task complexity do not affect audit judgment. From the results of this study, it can be concluded that auditor independence is an important factor in efforts to improve the quality of audit judgment.